Development of a Nomogram‐Based Online Calculator for Predicting Cancer‐Specific Survival in Patients With Digestive Tract Mixed Neuroendocrine‐Non‐Neuroendocrine Neoplasms (MiNENs): An Analysis of the SEER Database - Jing Tang; Siqi Wei; Guobin Tang; Ping Zhao (Cancer Reports)
ABSTRACT Aims Mixed neuroendocrine‐non‐neuroendocrine neoplasms (MiNENs) represent a rare and heterogeneous subgroup of neoplasms that typically consist of a neuroendocrine (NE) component, most commonly neuroendocrine carcinoma (NEC), alongside a non‐neuroendocrine (non‐NE) component. They commonly occur in the digestive tract, and their prognosis is influenced by multiple factors. This article aimed to identify factors that affect the cancer‐specific survival (CSS) of MiNENs and develop an effective nomogram‐based online calculator to validate its effectiveness. Methods The clinical, pathological, epidemiological, and survival data of patients with digestive tract MiNENs were collected from the Surveillance, Epidemiology, and End Results (SEER) database spanning from 2000 to 2020. Then, the dataset was divided into a training cohort and a validation cohort. The χ2 test or Fisher's exact test was utilized to assess differences in demographic and clinicopathological characteristics between the two groups. Kaplan–Meier survival curves and log‐rank tests were employed to conduct survival analysis. Additionally, univariate and multivariate Cox regression analyses were performed to identify potential prognostic factors and develop nomograms and an online calculator for predicting CSS at 1, 3, and 5 years. Lastly, the predictive ability of the online calculator was subsequently compared with the sixth edition of the American Joint Committee on Cancer (AJCC) TNM staging system using the Harrell concordance index (C‐index), the area under the receiver operating characteristic curve (AUC), calibration curve, and decision curve analysis (DCA). Results A total of 330 patients were randomly assigned to two groups, namely, the training cohort (n = 231) and the validation cohort (n = 99). The log‐rank test revealed a significant association between the lower cumulative survival and age ≥ 65 years, poor tumor grade, lack of surgical treatment, TNM stages III and IV, and distant metastasis. In the training cohort, a nomogram incorporating grade, surgery, TNM stage, and tumor metastasis was developed, which demonstrated favorable calibration and discriminatory capabilities. Compared to TNM staging, the nomogram exhibited satisfactory performance in predicting 1‐year, 3‐year, and 5‐year CSS rates. The C‐index value was 0.787 in the training cohort and 0.738 in the validation cohort, respectively. In the training cohort, the nomogram achieved an AUC of 85.81%, 85.86%, and 87.32% for 1‐year CSS, 3‐year CSS, and 5‐year CSS, respectively. In contrast, these AUC values were 78.46%, 81.50%, and 83.88% in the validation cohort, respectively. Conclusions The developed online calculator offers a novel approach to predicting the prognosis of patients with digestive tract MiNENs. Indeed, it can accurately predict the CSS of these patients over 1, 3, and 5 years, thereby assisting in enhancing prognosis and formulating appropriate treatment strategies.